Emergency Salpingo-Oophorectomy for Torsion of a Giant Mature Cystic Teratoma During the Second Trimester of Pregnancy: A Case Report - Muhammad Dezarino; Erika Kusumawardani; Fadhilah Zulfa; Doni Doni (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Ovarian torsion during pregnancy is a rare but serious condition that requires prompt diagnosis and intervention to prevent maternal and fetal complications. Large benign ovarian tumors, particularly mature cystic teratomas, are the most common underlying cause. This case report highlights the management of a giant torsed ovarian dermoid cyst detected in a pregnant woman during the second trimester.Case Illustration: A 16-year-old woman, G1P0A0, presented at 17–18 weeks of gestation with severe abdominal pain for one day. Physical examination revealed a mobile cystic adnexal mass. Ultrasonography showed a single live intrauterine fetus corresponding to gestational age and a unilocular left adnexal cyst measuring 14.5 × 12.7 × 11.5 cm with a positive whirlpool sign, indicating ovarian torsion. An emergency laparotomy with left salpingo-oophorectomy was performed. Histopathological examination confirmed a mature cystic teratoma with extensive necrosis and hemorrhage consistent with torsion, without evidence of malignancy. Ascitic and cyst fluid cytology showed benign lesions. The pregnancy was preserved, and postoperative fetal condition remained stable.Conclusion: This case demonstrates that prompt surgical intervention for ovarian torsion during the second trimester of pregnancy can be performed safely, allowing preservation of pregnancy and favorable maternal and fetal outcomes.Manajemen Torsio Ovarium Akibat Kista Dermoid Raksasa pada Trimester Kedua Kehamilan: Sebuah Laporan KasusAbstrakPendahuluan: Torsio ovarium selama kehamilan merupakan kondisi yang jarang, namun berpotensi serius dan memerlukan diagnosis serta penatalaksanaan yang cepat untuk mencegah komplikasi pada ibu dan janin. Tumor ovarium jinak berukuran besar, terutama mature cystic teratoma, merupakan penyebab tersering torsio ovarium. Laporan kasus ini menyoroti penatalaksanaan torsio ovarium akibat kista dermoid besar pada trimester kedua kehamilan.Ilustrasi Kasus: Seorang wanita berusia 16 tahun, G1P0A0, datang pada usia kehamilan 17 – 18 minggu dengan keluhan nyeri perut hebat sejak satu hari. Pemeriksaan fisik menunjukkan massa adneksa kistik yang mobile. Ultrasonografi menunjukkan janin tunggal hidup intrauterin sesuai usia kehamilan dan massa kistik unilokular pada adneksa kiri berukuran 14,5 × 12,7 × 11,5 cm dengan whirlpool sign positif yang mengarah ke torsio ovarium. Pasien menjalani laparotomi dan salpingo-ooforektomi kiri secara emergensi. Pemeriksaan histopatologi menunjukkan mature cystic teratoma dengan nekrosis dan perdarahan luas sesuai dengan torsio, tanpa tanda keganasan. Sitologi cairan asites dan kista menunjukkan lesi jinak. Kehamilan dapat dipertahankan dan kondisi janin pascaoperasi stabil.Kesimpulan: Kasus ini menunjukkan bahwa intervensi bedah yang cepat pada torsio ovarium trimester kedua dapat dilakukan dengan aman serta memberikan luaran maternal dan janin yang baik.